Diagnostic microbiology for intraocular infections: A comprehensive approach - Sanchita Mitra (Taiwan Journal of Ophthalmology, 2025)
Ocular infections, particularly intraocular infections, face challenges due to low sample volumes and their paucibacillary nature (low pathogen load) compared to other anatomical sites. This often leads to culture-negative cases, complicating the identification of the causative pathogen. Intraocular sample collection is mainly invasive and difficult to repeat. Ocular microbiology diagnostics require specialized expertise developed over years of experience, along with effective communication between clinicians and microbiologists, to ensure accurate pathogen diagnosis. This review offers an overview of ocular microbiology practices employing both conventional and molecular techniques for pathogen identification, including unusual pathogens primarily affecting the eye, antimicrobial susceptibility testing, result interpretation, emerging diagnostic techniques, challenges in intraocular sample processing, troubleshooting strategies, serological approaches, and basic operating room sterility assessments in eye care institutions. The review aims to assist both ophthalmologists and microbiologists in their daily practice of ocular microbiology diagnostics.